Strategi Resource-Based View (RBV) dalam Transformasi Mutu Literasi: Optimalisasi Modal Manusia dan Kearifan Lokal di SDN 181 Sukamiskin Kota Bandung - Mardianti, Fera; Ulfaturrohman, Nur Hidayah; Sugiyanto, Sugiyanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
This study analyzes the implementation of the Resource-Based View (RBV) strategy in improving literacy quality at SDN 181 Sukamiskin, Bandung City. Although the school possesses relatively strong teacher human capital and cultural capital, literacy achievement has declined, particularly in the advanced category. This study employs a qualitative descriptive approach using a case study method. Data were obtained from the 2024–2025 Education Report, the School-Based Curriculum, teacher profiles, and school policy documents. Data analysis was conducted using RBV-based SWOT analysis through the IFAS and EFAS matrices. The results indicate that the main problem lies in the suboptimal utilization of internal resources to support literacy improvement. Therefore, literacy enhancement strategies should be directed toward the integrated optimization of human capital and local wisdom. Keywords: Resource-Based View, Literacy Quality, Human Capital, Local Wisdom.